2018
DOI: 10.1242/dev.163907
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin signalling regulates organ identity via the AHK4 receptor in Arabidopsis

Abstract: Mutual interactions of the phytohormones, cytokinins and auxin determine root or shoot identity during postembryonic organogenesis in plants. However, our understanding of the role of hormonal metabolism and perception during early stages of cell fate reprogramming is still elusive. Here we show that auxin activates root formation, whereas cytokinins mediate early loss of the root identity, primordia disorganisation and initiation of shoot development. Exogenous and endogenous cytokinins influence the initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 78 publications
1
44
0
Order By: Relevance
“…The transgenic line TCSn::GFP 11 was used for all cell-sorting experiments, TCSn::GFP and TCS::GFP 28 were employed in protoplast and seedling treatment experiments, and the ecotype Col-0 was used for extraction of apoplast/symplast and for feeding experiments with labelled cytokinins. Crossed lines ahk/TCSn::GFP were published previously 26 and the mutant lines cre1-2 (ahk4 ) [14], ahk2-5, ahk3-7, ahk2-5 ahk3-7 (ahk2,3), ahk2-5 cre1-2 (ahk2,4 ) and ahk3-7 cre1-2 ( ahk3,4 ) 37 were crossed also with TCS::GFP. Homozygous lines were then identified and used in confocal experiments.…”
Section: Supplementary Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transgenic line TCSn::GFP 11 was used for all cell-sorting experiments, TCSn::GFP and TCS::GFP 28 were employed in protoplast and seedling treatment experiments, and the ecotype Col-0 was used for extraction of apoplast/symplast and for feeding experiments with labelled cytokinins. Crossed lines ahk/TCSn::GFP were published previously 26 and the mutant lines cre1-2 (ahk4 ) [14], ahk2-5, ahk3-7, ahk2-5 ahk3-7 (ahk2,3), ahk2-5 cre1-2 (ahk2,4 ) and ahk3-7 cre1-2 ( ahk3,4 ) 37 were crossed also with TCS::GFP. Homozygous lines were then identified and used in confocal experiments.…”
Section: Supplementary Methodsmentioning
confidence: 99%
“…iP had the strongest effect on meristematic stele cell initials, whereas tZ response was maximal in the transition zone in the stele. Although the exact biological role for cytokinins in the stele initials remains to be determined, TCS signal in those cells was absent in ahk4 mutant roots 26 (Supplementary Fig. 6c,d) providing genetic evidence for AHK4 being essential in cytokinin perception in the stele.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…T3 is closely linked to ETH and CTK-mediated pathways, which may be responsible for root swelling. It has been demonstrated that auxin activates root formation and that cytokinins mediate root identity, early primordial disintegration and early loss of bud development initiation [58]. CTKs are conducive to rhizome enlargement but not to rhizome induction.…”
Section: Discussionmentioning
confidence: 99%
“…T3 is closely linked to ETH and CTKmediated pathways, and it may be responsible for root swelling. It has been demonstrated that auxin activates root formation and that cytokinins mediate root identity, early primordial disintegration and early loss of bud development initiation [65]. CTKs are conducive to rhizome enlargement but not to rhizome induction.…”
Section: Discussionmentioning
confidence: 99%